Are You All right (AYA)? Association of cumulative traumatic events among Danish police officers with mental health, work environment and sickness absenteeism: protocol of a 3-year prospective cohort study. Issue 5 (24th May 2022) - Hansen, Nina Beck; Møller, Sara Rosenbeck; Elklit, Ask; Brandt, Lars; Andersen, Lars L; Pihl-Thingvad, Jesper
Abstract : Introduction: Police officers are frequently exposed to potentially traumatic events at work that increases risk of developing mental health problems, in particular post-traumatic stress disorder (PTSD). Individual and organisational factors may influence the detrimental effects of cumulative exposure to traumatic events. Occupational stress and lack of organisational support are associated with increased risk of PTSD among police officers. The Are You All right? (AYA) project is a prospective cohort study investigating the cumulative effect of traumatic events at work on mental health problems and absenteeism among police officers. The study also investigates whether potential risk and protective factors modify the association of traumatic events at work with mental health problems and absenteeism. Method and analysis: The AYA-study includes the entire Danish police force. Prospective survey data are collected over a 3-year period beginning in the spring of 2021. Electronic surveys are sent out at baseline with 1-year, 2-year and 3-year follow-up. Further, short surveys are sent out every third month, covering exposure to traumatic events and current mental health status. The survey data are paired with workplace register data on sickness absence. Register data on sickness absence cover the period from 2020 to 2025. Ethics and dissemination: This study was presented for evaluation at the National Ethics Committee in Denmark (reference number: 20202000-216), but according to Danish legislation, survey studies do not require approval by official Danish scientific or ethical committees. Participation in the project is based on informed consent, and data are handled in accordance with the Danish data legislation (journal number: 20/41457). Results are published in scientific journals and disseminated at international conferences.